PERSPEKTIF CRITICAL LEGAL STUDIE: FENOMENA VICTIM BLAMING TERHADAP PEREMPUAN KORBAN KEKERASAN SEKSUAL - Nurhayati Mardin (Sawerigading Law Journal, 2026)
This article discusses the existence of victims who should be the main subject of protection, but are often positioned as parties who are also at fault through stigma, moral stereotypes, and biased law enforcement practices where the law is not neutral, but is shaped by the tug-of-war between political and ideological interests that often reproduce social hierarchies and masculine biases in doctrine, standards of proof, and judicial practices. This normative legal research examines the national and international legal frameworks related to victim protection, including the TPKS Law, human rights instruments, and victimology doctrine, to show that victim protection is still abstract and not yet fully oriented towards the recovery and respect for the dignity of victims. Using a CLS approach and feminist critique, this article reveals that claims of legal neutrality often conceal masculine bias, including in standards of proof, testing the credibility of victims, and normalizing accusatory questioning in the courtroom. The results of the study show that the elimination of victim blaming is a prerequisite for procedural, substantive, and transformative justice, and requires an explicit legal reconstruction based on the perspective of victims and gender equality, including through the progressive implementation of PERMA No. 3 of 2017 and Law No. 12 of 2022 concerning TPKS. This article recommends a gender-responsive and trauma-informed approach, synchronization of technical guidelines between institutions, and strengthening of a legal paradigm that places victims at the center of justice, not merely as objects of the penal process